PENATALAKSANAAN RELINING PADA GIGI TIRUAN SEBAGIAN LEPASAN (GTSL) - Setiawan, Ricky (Jurnal Ilmiah Widya, 2013)
The purpose of making denture is to improve, to esthetic, masticator, speech function and to protect support tissue under the denture. Sometimes some patients complain about the lack retention and stabilization due to loose of the denture. The objective of this paper is to discuss the problem of the denture and the solutions. The methods used library research and the clinical experience. It can be concluded that to restore the retention and stabilization of partial dentures that are loose due to restoration of the residual ridge, denture relining is performed, by adding appropriate amount of new material onto the surface of the denture facing supporting tissue. In order to fill the existing space between the surface of the denture base and supporting tissues. The denture relining technique can be performed directly or indirectly.